Plasmon induced transparency and waveguide mode based optical biosensor for self-referencing sensing - Nidal El biyari; Ghita Zaz; Latifa Fakri Bouchet; Mohssin Zekriti (Sensors International)
In this paper, we present and investigate a novel approach for self-referenced sensing using a multilayer structure in Kretschmann configuration. The obtained results show that the structure can support two modes, plasmon-induced transparency and waveguide mode. The sensing performance of the structure was evaluated by calculating the sensor Sensitivity, Quality Factor, and Figure of Merit. Moreover, to quantify the capability of our approach for self-referencing sensing we calculated the self-referencing figure of merit. We demonstrate that the PIT mode-based approach has the best simulation results in terms of Figure of Merit of 5950/RIU, Quality Factor of 292.5/RIU, and Self-Referencing Figure of Merit of 5.7. The designed biosensors can be used for accurate and reliable sensing applications.